Ultrasonic Mammography with Circular Transducer Array - OPIELIŃSKI, Krzysztof J.; PRUCHNICKI, Piotr; GUDRA, Tadeusz (Archives of Acoustics, 2014)
Ultrasonic projection imaging is similar to X-ray radiography. Nowadays, ultrasonic projection methods have been developed in the set-up of multi-element flat arrays with miniature transducers, where one of the array acts as a transmitter and the other one is a receiver. In the paper, a new method of the projection imaging using a 1024-element circular ultrasonic transducer array was presented. It allows the choice of a projection scanning plane for any angle around a studied object submerged in water. Fast acquisition of measurement data is achieved as a result of parallel switching of opposite transmitting and receiving transducers in the circular array and vertical movement of the array. The algorithm equalizing the length of measurement rays and distances between them was elaborated for the reconstruction of projection images. Projection research results of breast phantom obtained by means of the elaborated measurement set-up and compared with mammography simulations (acquired through overlapping of X-ray tomographic images) show that ultrasonic projection method presented in this paper (so-called ultrasonic mammography) can be applied to the woman’s breast and be used as a diagnosis for an early detection of cancerous lesions. It can, most of all, be used as an alternative or complementary method to standard mammography, which is harmful because of ionizing radiation and invasive because of the mechanical compression of tissue.